2008
DOI: 10.4103/0970-0358.41104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of melatonin on the proliferation and differentiation of rat adipose-derived stem cells

Abstract: Background:Osteogenesis driven by adipose-derived stem cells (ADSCs) is regulated by physiological and pathological factors. Accumulating evidence from in vitro and in vivo experiments suggests that melatonin may have an influence on bone formation. However, little is known about the effects of melatonin on osteogenesis, which thus remains to be elucidated. This study was performed to determine whether melatonin at physiological concentrations (0.01-10 nM) could affect the in vitro proliferation and osteogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Previous studies demonstrated that the role of melatonin in the regulation of cell proliferation dependents on concentration and exposure time as well as cell type and species 39 , 40 . For example, melatonin has no significant effect on bovine granulosa cell proliferation 41 but significantly promotes the proliferation of porcine granulosa cells 42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that the role of melatonin in the regulation of cell proliferation dependents on concentration and exposure time as well as cell type and species 39 , 40 . For example, melatonin has no significant effect on bovine granulosa cell proliferation 41 but significantly promotes the proliferation of porcine granulosa cells 42 .…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, numerous physiological roles of melatonin are mediated via activation of two high-affinity G protein-coupled receptors, MT1 and MT2 28 , 29 . MT1 and MT2 mediate the physiological role of melatonin in a manner dependent on melatonin concentration and exposure time, as well as cell type 39 , 40 . We found co-expression of MT1 and MT2 in BIPs and reported that MT2 expression exhibited significant differences during BIPs differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The age-related decrease of melatonin production could shift the bone marrow cells differentiation from osteoblastic differentiation toward an adipocytic line of cell, which could explain the development of osteoporosis during aging [ 37 ]. Melatonin also promotes the osteogenic differentiation of bone marrow stem cells whereas it has negative effects on differentiation of adipose-derived stem cells [ 38 , 39 ].…”
Section: Melatonin and Bone Physiologymentioning
confidence: 99%
“…17 These features make them of great potential in the management of a large number of diseases, especially degenerative conditions, 18 including skin exposed to injury or disease. Functional stem cells are present throughout all layers of the skin, they enable skin regeneration through their physical and chemical signals, 19 yet it is somehow limited.…”
Section: Introductionmentioning
confidence: 99%